2021
DOI: 10.1248/bpb.b20-00604
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate Provides Neuroprotection against Cerebral Ischemia–Reperfusion Injury <i>via</i> the TLR-4/NF-κB Pathway in Rats

Abstract: Inflammation has an important role in ischemia/reperfusion (I/R) injury. Artesunate (ART) has anti-microbial and anti-inflammatory pharmacological activities, and it is used for various types of serious malaria, including cerebral malaria. ART maintains a high concentration in the brain but little is known about the neuroprotective effect of ART against brain I/R injury. We studied the neuroprotection of ART against brain I/R injury and its underlying mechanism. In this study, rats were subjected to middle cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Several artemisinin derivatives revealed anti-inflammatory effects in the neurological system. 13,27 Moreover, ELISA results showed that artesunate inhibited the levels of the M1-related inflammatory IL-1β and TNF-α in ICH rats. In summary, ICH injury in SD rats is associated with microglial overactivation and M1-related inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several artemisinin derivatives revealed anti-inflammatory effects in the neurological system. 13,27 Moreover, ELISA results showed that artesunate inhibited the levels of the M1-related inflammatory IL-1β and TNF-α in ICH rats. In summary, ICH injury in SD rats is associated with microglial overactivation and M1-related inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a previous study, we found that artesunate significantly alleviated ICH injury in rats, as shown by neurological deficits, haematoma volume and brain oedema. Several artemisinin derivatives revealed anti‐inflammatory effects in the neurological system 13,27 . Moreover, ELISA results showed that artesunate inhibited the levels of the M1‐related inflammatory IL‐1β and TNF‐α in ICH rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao X demonstrated that artemisinin modulated the TLR4/NF-κB signaling and delayed microglia’s activation of immune-inflammatory responses by microglia ( Zhao et al, 2022 ). Chen et al (2021b) exhibited that ART reduced the expression of TLR-4, MyD88, NF-κB, TNF-α, and IL-6 in ischemic cortical regions through the TLR-4/NF-κB pathway. Chen YX confirmed that ART could reduce the expression levels of TLR4, p-NF-κB, p-p38, Bcl2 associated X (Bax), and caspase-9, increase the expression of B cell lymphoma-2 (Bcl-2) in a dose-dependent manner, inhibit the TLR4/NF-κB signaling pathway, and downregulate the levels of TNF-α, IL-8 and interferon-gamma (IFN-γ) ( Chen et al, 2019 ).…”
Section: Role Of Artemisinin and Its Derivatives In Kidney Diseasementioning
confidence: 97%